2022
DOI: 10.1111/nyas.14887
|View full text |Cite
|
Sign up to set email alerts
|

Drought–heatwave nexus in Brazil and related impacts on health and fires: A comprehensive review

Abstract: Climate change is drastically altering the frequency, duration, and severity of compound drought‐heatwave (CDHW) episodes, which present a new challenge in environmental and socioeconomic sectors. These threats are of particular importance in low‐income regions with growing populations, fragile infrastructure, and threatened ecosystems. This review synthesizes emerging progress in the understanding of CDHW patterns in Brazil while providing insights about the impacts on fire occurrence and public health. Evide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 205 publications
0
20
0
1
Order By: Relevance
“…Atividades locais e regionais de queima de biomassa e de modificação de uso do solo influenciam as mudanças no comportamento de eventos extremos pela alteração no ciclo hidrológico e balanço de energia e, consequentemente, as circulações atmosféricas associadas (IPCC, 2013). Há evidências de que as ondas de calor estão se tornando cada vez mais ligadas às secas no Nordeste, Sudeste, Amazônia e no Pantanal brasileiro (Libonati et al, 2022).…”
Section: Resultados E Discussõesunclassified
“…Atividades locais e regionais de queima de biomassa e de modificação de uso do solo influenciam as mudanças no comportamento de eventos extremos pela alteração no ciclo hidrológico e balanço de energia e, consequentemente, as circulações atmosféricas associadas (IPCC, 2013). Há evidências de que as ondas de calor estão se tornando cada vez mais ligadas às secas no Nordeste, Sudeste, Amazônia e no Pantanal brasileiro (Libonati et al, 2022).…”
Section: Resultados E Discussõesunclassified
“…To the best of our knowledge, few epidemiological studies of heat waves-related mortality have been conducted in Brazil [12,13]. One multi-city study examined the impacts of heat waves on all-cause mortality and reported the results at national level [14].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding cardiovascular diseases, the fraction of deaths attributed to heat stress, with a global warming of +4 • C, is predicted to be 40% in the Northern, 35% in the Northeastern, and 25% in Center-West capitals [16]. Heat waves have already been responsible for increased mortality and preterm births during record-breaking droughts in southeastern Brazil between 2013 and 2015 [17]. In Brazil, heat exposure is associated with an increase in all-cause hospitalizations and those due to ischemic heart disease, asthma, pneumonia, renal diseases, mental health conditions, and neoplasms, impacting the demand for medical and surgical care [18].…”
Section: Introductionmentioning
confidence: 99%